Exploratory Item Factor Analysis: Some additional considerations. - Ferrando, Pere J.; Lorenzo-Seva, Urbano (Anales de Psicología / Annals of Psychology, 2014)
This article can be considered to be an extension of a previous work by Lloret et al. (2014) in which we discuss in more depth two particularly relevant topics in item factor analysis: (a) how to chose the most appropriate correlation matrix, and (b) how to arrive at a realistic and interpretable semi-confirmatory solution by making use of the available information. The discussion of these topics strongly reflects the views of the authors. So, we encourage the interested reader to take it critically. For both topics we offer practical recommendations. However, the article is mainly intended for applied researchers with a certain methodological penchant and who want to go beyond standard recommendations.